PENGUATAN KAPASITAS GURU DAN SISWA DALAM PEMANFAATAN TEKNOLOGI DIGITAL - Wahyu ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2025)
The advancement of digital technology encourages the world of education to adapt, including increasing the capacity of teachers and students in integrating technology into learning. Unfortunately, there are still many schools that are not ready, both in terms of skills and infrastructure. Community service activities at SMP Al-Khairiyah Cilegon aim to improve the ability of teachers and students to use technology effectively and wisely. The implementation method includes identifying needs, workshops, mentoring, and evaluation. Teachers are trained to use online platforms and manage virtual classes. The results show an increase in digital skills and enthusiasm for learning. This activity makes a real contribution to the digital transformation of schools and opens up opportunities for further coaching through the internal digital literacy team